Synthesis, structural and optical properties of mesostructured, X-doped NiO (x = Zn, Sn, Fe) nanoflake network films. (July 2020) - Mamat, M.H.; Parimon, N.; Ismail, A.S.; Shameem Banu, I.B.; Sathik Basha, S.; Rani, R.A.; Zoolfakar, A.S.; Malek, M.F.; Suriani, A.B.; Ahmad, M.K.; Rusop, M.
Graphical abstract: Highlights: Mesostructured NiO nanoflake network films were directly grown on ITO glass. The growth mechanism of NiO nanoflake network film was proposed. Study the structural and optical anomalies of doped NiO nanoflake network films. The effects of Zn, Sn, and Fe dopants on NiO film characteristics have been studied. Correlation between optical and structural characteristics have been investigated. Abstract: Mesostructured nickel oxide (NiO) nanoflake network films doped with zinc (Zn), tin (Sn), and iron (Fe), were grown by a one-step solution immersion method at 120⁰C on indium-doped tin oxide (ITO) glass substrates. Field emission scanning electron microscope images revealed that the NiO nanoflake networks doped with Zn, Sn, and Fe, grew on the ITO but with different nanoflake morphologies and thicknesses, and their growth mechanisms are discussed. The X-ray diffraction patterns show that all grown films exhibited polycrystalline NiO structures. Substantial modifications and anomalies in the NiO film's morphology, thickness, lattice constant, stress/strain, crystallite size, and dislocation density, were observed when doped with the different sources. The optical and electrical properties also altered after the doping process. The Raman spectra indicated that all the films exhibited cubic NiO structures with paramagnetic characteristics. Moreover, the characteristic deviations in the doped NiO nanoflake network films have been thoroughly discussed.